The global green economy: a review of concepts, definitions, measurement methodologies and their interactions. Issue 1 (20th April 2017) - Georgeson, Lucien; Maslin, Mark; Poessinouw, Martyn
Abstract : Over the past decade, the green economy has emerged as an important policy framework for sustainable development in both developed and developing countries. It presents an attractive framework to deliver more resource efficient, lower carbon, less environmentally damaging, more socially inclusive societies. There are tensions between competing green economy discourses and a number of different definitions exist, all of which have major shortcomings. This is further complicated by the different underlying concepts of the 'weak', 'transformational' and 'strong' green economy. Several important definitions focus on the aspirational 'transformational green economy'. To enable and to track this 'transformation', economic and environmental measurement is essential. Current approaches are still in development, lack available data or show inconsistencies with proposed definitions, and thus may neither support effective decision‐making nor efforts to transform economies. This review identifies these current shortcomings and makes four overarching recommendations for improving measurement for green economy transformations, including cheaper, faster and more widely available data, and broader frameworks for measuring economy–society–environment interactions. We suggest that proper measurement of the green economy needs to move beyond GDP as the central measure of progress and to better track the 'transformational green economy'. This will enable the green economy to become relevant again at national and international levels, given the emerging Sustainable Development Goals and post‐COP 21 frameworks. Abstract : The green economy has emerged as an important policy framework for sustainable development, but tensions and shortcomings exist within green economy discourses and definitions. For a green economy 'transformation', economic and environmental measurement is essential; current approaches are still in development, lack available data or show inconsistencies with proposed definitions. This review identifies these current shortcomings and makes four recommendations for improving measurement of green economy transformation, to enable the green economy to become relevant again under the emerging Sustainable Development Goals (SDGs) and post‐COP 21 framework. e00036